2022
DOI: 10.1111/spol.12803
|View full text |Cite
|
Sign up to set email alerts
|

Mediating the claim? How ‘local ecosystems of support’ shape the operation and experience of UK social security

Abstract: Local state and third sector actors routinely provide support to help people navigate their right to social security and mediate their chequered relationship to it. COVID‐19 has not only underlined the significance of these actors in the claims‐making process, but also just how vulnerable those working within ‘local ecosystems of support’ are to external shocks and their own internal pressures. Drawing on qualitative fieldwork with organisations providing support to benefit claimants and those financially stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Because DWP rarely helps individuals navigate the program's interface, claimants rely on outside agencies and family members for assistance. Claimants must therefore become experts in navigating the wide web of actors beyond DWP who might help them interact with the Universal Credit system (Edmiston et al 2022). Likewise, front-line officials often describe interfaces as intensifying the technical aspects of their work.…”
Section: Smooth Operators: Interface Governance and Its Intended Effectsmentioning
confidence: 99%
“…Because DWP rarely helps individuals navigate the program's interface, claimants rely on outside agencies and family members for assistance. Claimants must therefore become experts in navigating the wide web of actors beyond DWP who might help them interact with the Universal Credit system (Edmiston et al 2022). Likewise, front-line officials often describe interfaces as intensifying the technical aspects of their work.…”
Section: Smooth Operators: Interface Governance and Its Intended Effectsmentioning
confidence: 99%
“…There are, however, risks in drawing inferences from such sources without recognition that linked datasets can introduce new sources of measurement error, and invariably only cover the target sample of income surveys (usually private households) rather than the wider low-income population. Equally, a sole emphasis on the use of administrative records misses those ineligible for, or on the periphery of, social security support such as those with No Recourse to Public Funds or the ‘missing workless’ not claiming benefits (Edmiston et al, 2022b; Shildrick et al, 2012). Indeed, distributional analyses employing ‘improved measures, higher-quality data and several thresholds’ that go some way to addressing these issues find that deeper forms of poverty are likely underestimated, particularly when accounting for homeless populations (Brady & Parolin, 2020, p. 2338).…”
Section: Building On Sand: Poor Data Coverage and Qualitymentioning
confidence: 99%
“…It is suggested that people's willingness to claim social assistance is shaped by the administration of case managers' assessments and the extent to which policy is customised to clients' needs at the local level (De Wilde & Marchal, 2019; Edmiston et al, 2022). Thus, a multi‐level institutional analysis of claimants' experiences displays actors' aggregated moves and meaning‐making processes in relation to the welfare systems (Gřundělová, 2021; Rice, 2013).…”
Section: A Multi‐level Institutional Approach To Welfare Claiming Exp...mentioning
confidence: 99%